2015
DOI: 10.5863/1551-6776-20.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enoxaparin Dosing and Monitoring in Pediatric Patients at Children's Teaching Hospital

Abstract: OBJECTIVES: The primary objective of this study was to evaluate whether empirical enoxaparin doses according to Chest guidelines resulted in therapeutic antifactor Xa concentrations in pediatric patients. Secondary objectives were to determine the median enoxaparin dose that resulted in therapeutic anticoagulation, the median time to therapeutic concentrations, and the percentage of patients who experienced major bleeding. METHODS: Patients in a tertiary medical center who were <18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…However, bleeding events may have occurred outside of this time frame and may have been missed if they did not result in a hemoglobin decrease of >2 mg/dL or red blood cell or platelet transfusion, or if they were not documented in daily progress notes. Similar studies have identified major bleeding events in 0% to 2.6% of infants and children receiving enoxaparin for the treatment of thrombosis 6,8,9. The lack of identification of major bleeding events in our population within 1 week of therapeutic attainment supports the safety of enoxaparin in the treatment of thrombosis in infants and children even when doses are escalated above 1 mg/kg SQ every 12 hours.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…However, bleeding events may have occurred outside of this time frame and may have been missed if they did not result in a hemoglobin decrease of >2 mg/dL or red blood cell or platelet transfusion, or if they were not documented in daily progress notes. Similar studies have identified major bleeding events in 0% to 2.6% of infants and children receiving enoxaparin for the treatment of thrombosis 6,8,9. The lack of identification of major bleeding events in our population within 1 week of therapeutic attainment supports the safety of enoxaparin in the treatment of thrombosis in infants and children even when doses are escalated above 1 mg/kg SQ every 12 hours.…”
Section: Discussionsupporting
confidence: 73%
“…Our results are consistent with previous retrospective studies of a similar design and with similar populations. McCormick and colleagues found that infants 60 days to 1 year of age required median enoxaparin doses of 1.5, 1.35, and 1.37 mg/kg, respectively 6,8,10. The number of infants between 60 days and 1 year of age in these studies ranged from 10 to 30 patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although there are multiple studies and data that support enoxaparin dosing for VTE prophylaxis and treatment, as summarized by the CHEST guidelines, questions still remain on how the hypermetabolic state of burn patients affects medication dosing. McCormick et al 8 suggest that the standard dosing set forth by CHEST provides inadequate anti-Xa concentrations. With respect to the pediatric population, Brown et al 2 prospectively evaluated 35 pediatric burn patients to determine if 0.5 mg/kg of SC enoxaparin, dosed twice daily, would result in anti-Xa concentrations between 0.2 and 0.4 units/mL.…”
Section: Discussionmentioning
confidence: 99%